Preferences and barriers to the utilization of primary health care by sick physicians: a nationwide survey. (25th August 2020) - Zacay, Galia; Baron-Epel, Orna; Malatskey, Lilach; Heymann, Anthony
Abstract: Background: Physicians are often dissatisfied with their own medical care. Self-prescribing is common despite established guidelines that discourage this practice. From a pilot study, we know primary care physicians' (PCP) preferences, but we lack information regarding other specialties and work places. Objectives: The goal of this study was to examine whether physicians are satisfied with their personal primary care and how this could be improved. Methods: We distributed an electronic survey to all physicians registered with the Israeli Medical Association. The questionnaire examined satisfaction with medical care, preferences for using formal care versus informal care, self-prescribing and barriers to using formal care. Results: Two thousand three hundred and five out of 24 360 invited physicians responded. Fifty-six per cent of the respondents were satisfied with their personal primary care. Fifty-two per cent reported initiating self-treatment with a medication during the last year. Five and four per cent initiated treatment with a benzodiazepine and an antidepressant, respectively, during the last year. This was despite the fact that most physicians did not feel competent to treat themselves. Having a personal PCP was correlated with both a desire to use formal care and self-referral to formal care in practice. Regression analysis showed that the highest odds ratio (OR) for experiencing a large gap between desired and actual care were for physicians who had no personal PCP (OR = 1.92). Conclusions: Physicians frequently engage in self-treatment and in informal medical care. Whether the root cause is the health care system structure that does not meet their needs or the convenience of self-treatment is not known.